Konstruksi Pemahaman Jamaah Majelis Zikir Al-Khidmah Terhadap Sakralitas Banyu Mana>qib - Abd. Basyid; M. Yusuf (IAIN Ponorogo, 2020)
Abstract: This article aims to describe how the construction of the congregation's understanding of the al-Khidmah zikir assembly about the sacredness of banyu mana> qib so that it influences and moves the congregation to put water around the assembly. To answer these questions, the author uses a qualitative research methodology with analysis using the theory of Peter L. Berger and Thomas Luckman about social construction. The construction of the understanding of the congregation of the Al-Khidmah zikir assembly when viewed with Berger and Luckman's theory will take place through dialegical interactions of subjective reality, symbolic reality, and objective reality. Subjective reality in this theory, each individual believes that the reading of mana>qib is a source of value. After that, it is symbolically represented - symbolic reality - by placing water around the qib. Then the combination of each individual raises an objective reality about banyu mana>qib. Simultaneously there is also a process of externalization, objectification, and iternalization. The externalization process occurs when the congregation adjusts to the values that have developed among the congregation. Then the objectification is marked by the congregation who has the same understanding and perception, namely, banyu mana> qib which is able to provide properties as a healing medium. Finally, the congregation identifies itself (internalization) about the needs they want to fulfill through / because of the water, so that an action appears.الملخص: يهدف هذا المقال إلى دراسة كيفية بناء فهم مجمع ذكر الخدمت على قدسية مياه المناقب وبالتالي التأثير على المصلين وتحريكهم لوضع الماء حول التجمع. للإجابة على هذا السؤال ، يستخدم المؤلف منهجية بحث نوعي مع التحليل باستخدام نظرية بيتر ل.بيرجر وتوماس لاكمان في البناء الاجتماعي. إن بناء فهم مجمع ذكرى الخدمتة ، إذا ما نظر إليه بنظرية بيرغر ولوكمان ، سيتم من خلال التفاعل الديالكتيكي للواقع الذاتي والواقع الرمزي والواقع الموضوعي. الحقيقة الذاتية في هذه النظرية ، يعتقد كل فرد أن قراءة المناقب مصدر قيمة. بعد ذلك يتم تمثيلها رمزياً - الواقع الرمزي - بوضع الماء حول مكان قراءة المناقب. ثم يؤدي الجمع بين كل فرد إلى إحضار حقيقة موضوعية حول مناقب المياه. في الوقت نفسه ، هناك أيضًا عملية المبالغة والتشكيل والإمالة. تحدث عملية التخارج عندما تتكيف الجماعة مع القيم التي نشأت بين المصلين. ثم يتم تمييز التشيؤ من قبل المصلين الذين لديهم نفس الفهم والإدراك ، أي مياه المناقب القادرة على توفير الفعالية كوسيلة للشفاء. أخيرًا ، يعرّف المصلين أنفسهم (مستوطنين) حول الاحتياجات التي يريدون تلبيتها من خلال / بسبب الماء ، بحيث ينشأ فعل ما.Abstrak: Artikel ini bertujuan untuk mengungkapkan bagaimana konstruksi pemahaman jamaah majelis zikir Al-Khidmah tentang sakralitas banyu mana>qib sehingga mempengaruhi dan menggerakan jamaah untuk meletakkan air di sekitar majelis. Untuk menjawab pertanyaan tersebut, penulis menggunakan metodologi penelitian kualitatif dengan analisis menggunakan teori Peter L. Berger dan Thomas Luckman tentang konstruksi sosial. Konstruksi pemahaman jamaah majelis zikir Al-Khidmah jika dilihat dengan teori Berger dan Luckman maka akan berlangsung melalui interaksi dialegtis dari subjective reality, symbolic reality, dan objective reality. Subjective reality dalam teori ini, masing-masing individu meyakini bahwa bacaan manaqib adalah sumber nilai. Setelah itu direpresentasikan secara simbolis –symbolic reality- dengan meletakkan air di sekitar tempat pembacaan mana>qib. Kemudian gabungan masing-masing individu memunculkan satu objective reality tentang banyu mana>qib. Secara simultan juga terjadi proses eksteralisasi, objektifikasi, dan iternalisasi. Proses eksternalisasi terjadi ketika jamaah menyesuaikan diri dengan nilai yang sudah berkembang di kalangan jamaah. Kemudian objektifikasi ditandai dengan jamaah yang memiliki pemahaman dan presepsi yang sama, yakni, banyu mana>qib yang mampu memberikan khasiat sebagai media penyembuhan. Terakhir, jamaah mengidentifikasi dirinya (internalisasi) tentang kebutuhan yang hendak mereka penuhi melalui/lantaran air tersebut, sehingga muncul suatu tindakan.